Child sexual abuse: is there any sufficient protection for our children? / Adibah Abdul Kadir…[et al.] - Abdul Kadir, Adibah; Aqbal Omar, Farah Qurashiyah; Nasarudin, Intan Noorashikin; Yahya Bujang, Nur Ruhaizat (Faculty of Law, 2006)
For the last two semesters, we have been conducting a research on child sexual abuse in Malaysia. We concentrated on punishment which laid down in Section 376 of the Penal Code (Act 574) against the child rapist. In our research, we alsotouched and discussed about sexual trade among children in the South East Asian country. We strongly believed that person who involved in this should be punished more severely. Also we believe that there should be specific punishment against the child rapist because thee is not enough protection for our children. We have conducted a survey on child sexual abuse by distributing it to 50 respondents. We also consulted the police officer in charged to get the statistic of cases regarding child sexual abuse in Shah Alam. We are glad that all the respondents looked at this issue seriously and gave their opinion and ways to decrease the cases of child sexual abuse. Among the few important questions that were raised in the questionnaire was whether the respondent had ever heard about cases concerning child rape?